Plasma miRNA-223 correlates with risk, inflammatory markers as well as prognosis in sepsis patients. Issue 27 (July 2018) - Wu, Xiaoling; Yang, Junhui; Yu, Li; Long, Ding
Abstract : Abstract: The purpose was to evaluate the role of plasma microRNA-223 (miRNA-223) in risk and prognosis in sepsis patients, and its correlation with inflammatory markers. In this study, 187 sepsis patients from July 2015 to December 2016 were consecutively enrolled. Blood samples from septic patients and healthy controls (HCs) were collected, and plasma was separated for miRNA-223 expression detected by quantitative real-time PCR (qPCR). Enzyme-linked immune sorbent assay (ELISA) was performed to detect inflammatory markers. The results were as follows: miRNA-223 was highly expressed in sepsis patients compared to HCs ( P  < .001). Receiver operating characteristic (ROC) curve revealed miRNA-223 disclosed a good diagnostic value of sepsis with area under curve (AUC) of 0.754, 95% CI: 0.706–0.803. Sensitivity and specificity were 56.6% and 86.6% at the best cut-off point, respectively. Multivariate logistic analysis indicated that miRNA-223 could predict sepsis risk independently. Spearman's correlation disclosed that miRNA-223 relatively expression positively correlated with APCHE II score (r = 0.459, P < 0.001), CRP (r = 0.326, P < 0.001), TNFα (r = 0.325, P < 0.001), IL-1β (r = 0.165, P = 0.024), IL-6 (r = 0.229, P = 0.002) and IL-8 (r = 0.154, P = 0.035), while it was negatively correlated with IL-10 (r = -0.289, P < 0.001). miRNA-223 expression in non-survivor was higher than that in survivor (P < 0.001). ROC curve revealed miRNA-223 could distinguish sepsis non-survivor form survivor with AUC of 0.600, 95% CI: 0.505–0.695. Sensitivity and specificity were 83.5% and 38.9% respectively at the best cut-off point. In conclusion, plasma miRNA-223 correlates with disease severity and inflammatory markers levels, and it might serve as a novel diagnostic and prognostic biomarker in sepsis patients. Abstract : Supplemental Digital Content is available in the text